2018
DOI: 10.1590/1678-4685-gmb-2017-0169
|View full text |Cite
|
Sign up to set email alerts
|

An association study of FOXO3 variant and longevity

Abstract: Human longevity is a polygenic and multifactorial trait. Pathways related to lifespan are complex and involve molecular, cellular, and environmental processes. In this analytical observational study, we evaluated the relationship between environment factors, oxidative stress status, DNA integrity level, and the association of FOXO3 (rs2802292), SOD2 (rs4880), APOE (rs429358 and rs7412), and SIRT1 (rs2273773) polymorphisms with longevity in oldest-old individuals from southeastern Brazil. We found an associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(67 reference statements)
0
6
1
Order By: Relevance
“…Statistics showed a significant relationship between the FOXO3 and the urban/rural split. Gender-specific analysis revealed that only females showed the effects of the FOXO3, whereas males did not, due to the lower levels of the FOXO3 phosphorylation in females [42][43][44][45]. Our findings on CRC however, could not find such a sexual dimorphic pattern.…”
Section: Discussioncontrasting
confidence: 75%
“…Statistics showed a significant relationship between the FOXO3 and the urban/rural split. Gender-specific analysis revealed that only females showed the effects of the FOXO3, whereas males did not, due to the lower levels of the FOXO3 phosphorylation in females [42][43][44][45]. Our findings on CRC however, could not find such a sexual dimorphic pattern.…”
Section: Discussioncontrasting
confidence: 75%
“…FOXO3 is active when insulin/IGF signaling is reduced and upregulates genes involved in stress resistance and protein homeostasis ( Figure 2) (Martins et al, 2016;Webb and Brunet, 2014). Consistent with the pro-longevity role of this transcription factor, FOXO3 SNPs are associated with an increase in FOXO3 expression (Flachsbart et al, 2017), which could in turn promote stress resistance (Li et al, 2016;Silva-Sena et al, 2018). These studies indicate that nutrient-sensing pathways, which regulate lifespan in model organisms, are also likely critical for human longevity.…”
Section: Human Genetics Of Longevity Candidate Gene Studiesmentioning
confidence: 80%
“…The first study on a Brazilian cohort, including 220 individuals of at least 85 years of age and 232 controls averaging 72 years, was recently performed to investigate the association between FOXO3 , SOD2 , SIRT1, and APOE known variants and several phenotypes in oldest-olds. Only an association of two FOXO3 alleles with gender and triglyceride levels was confirmed in this case and the authors suggested expansion of the number of samples in order to perform a more powerful analysis [140].…”
Section: Apoe and Human Longevitymentioning
confidence: 98%